Kajian Yuridis Terhadap Putusan Isbat Nikah Poligami Pegawai Negeri Sipil - Inayah, Nurul; Ismail, Syawaluddin (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Lhokseumawe, 2019)
The isbat nikah polygamy issue is one of the effects of the legal dualism between the obligation to register marriage and the ability of marriage certificate for marriages which are not listed as stipulated in the Indonesian marriage law. One example of the decision to request isbat nikah polygamy is the decision Religion Court of Bima No. 0663 / Pdt.G / 2014 / PA.Bm. jo. the decision of the High Court Religion of Mataram No. 0093 / Pdt.G / 2014 / PTA.Mtr. This paper looks at the two decisions judicially. The results of this research indicated that decision No. 0663 / Pdt.G / 2014 / PA.Bm. jo verdict No. 0093 / Pdt.G / 2014 / PTA.Mtr legally the submission of isbat nikah polygamy contradictory to the applicable of polygamy law. The granting of marriage license for Sirri polygamy marriage is not justified for any reason. This is then expressly regulated in SEMA No. 3 of 2018 2018 concerning the Imposition of the 2018 Supreme Court Chamber Plenary Results Formulation as a Guideline for the Implementation of Tasks for the Court stating that the request for isbat nikah polygamy is must be declared not accepted even though it was submitted on the child's grounds, and for the benefit of the child can submit a determination of the child's origin.